2015
DOI: 10.1016/j.apcata.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Selective transformation of glucose into propylene glycol on Ru/C catalysts combined with ZnO under low hydrogen pressures

Abstract: a b s t r a c tRecently, biomass resources have garnered significant attention as sustainable and renewable raw materials for the production of chemicals. Propylene glycol (PG) is a valuable chemical product that can be synthesized from biomass. Herein, the selective transformation of glucose into PG was investigated on a carbon-supported 5 wt% Ru catalyst (5%-Ru/C) combined with solid acid-base catalysts under low hydrogen pressures. The reaction conditions, namely the amount of ZnO, temperature, and hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 48 publications
2
34
3
Order By: Relevance
“…Yet, previous studies have reported that the combination of Cu and ZnO was active and selective in the hydrogenolysis of alditols to glycols [21,[36][37][38]. The activity of Ru-(Mn-Zr)O X and Ru-(Mn-Ti)O X catalysts was 33 h −1 , i.e., lower than the activity of Ru-(Mn-Al)O X (57 h −1 ).…”
Section: Hydrogenolysis Of Xylitolmentioning
confidence: 76%
See 1 more Smart Citation
“…Yet, previous studies have reported that the combination of Cu and ZnO was active and selective in the hydrogenolysis of alditols to glycols [21,[36][37][38]. The activity of Ru-(Mn-Zr)O X and Ru-(Mn-Ti)O X catalysts was 33 h −1 , i.e., lower than the activity of Ru-(Mn-Al)O X (57 h −1 ).…”
Section: Hydrogenolysis Of Xylitolmentioning
confidence: 76%
“…This observation suggests that TiO 2 and ZrO 2 were amorphous, unlike in a Cu-ZrO 2 -MgO material obtained after similar thermal treatment [31]. It is worth noting that the pattern of Ru-(Mn-Al)O X recorded with a higher time per step ( Figure A1) exhibited peaks associated with Mn 3 O 4 in the 2θ region of [28][29][30][31][32][33][34][35][36][37][38] • . This phase might also be present in the other Ru-(Mn-M)O X .…”
Section: Catalyst Characterizationmentioning
confidence: 92%
“…The synthetic trees for 1,2-PD derivatives have been made up starting from bioglycerol-derived propylene glycol. Although there are precedents for a one-step 1,2-PD synthesis by a retroaldol glucose conversion [61,62], currently only the glycerol hydrogenolysis process is employed on an industrial scale. Carbohydrate fermentation is supposed to be an appropriate source of the renewable acetone.…”
Section: The Characterization Of the Productsmentioning
confidence: 99%
“…Carbohydrate fermentation is supposed to be an appropriate source of the renewable acetone. The synthesis of TMD is implemented via the direct ketalization of 1,2-PD with acetone, since the feasibility of the one-step 1,2-PD to TMD conversion seems to be rather arguable in essence, Although there are precedents for a one-step 1,2-PD synthesis by a retroaldol glucose conversion [61,62], currently only the glycerol hydrogenolysis process is employed on an industrial scale. Carbohydrate fermentation is supposed to be an appropriate source of the renewable acetone.…”
Section: The Characterization Of the Productsmentioning
confidence: 99%
“…It is also known that side pathways yield alkanes from the alkyl chain of alcohols [171], thus lowering hydrogen yield. It is worth noting that these alcohols can be obtained from biomass through chemical [253][254][255] or biochemical [256] processes, while glycerol is an abundant by-product of the biodiesel industry [257]. Other organic compounds have been also used, such as carboxylic acids and aldehydes, since they constitute bio-oil [258] and wastewater [259].…”
Section: Reaction Conditionsmentioning
confidence: 99%